Los Angeles County Juvenile Justice Crime Prevention Act Fiscal Year 2009-2010 Report - Fain, Terry (RAND Corporation, 2012)
The Juvenile Justice Crime Prevention Act funds programs that have been proven effective in curbing crime among juvenile probationers and young at-risk offenders. This report summarizes, for fiscal year 2009-2010, Corrections Standards Authority-mandated outcome measures from each of the programs, as well as county-determined supplemental outcomes.